KEHADIRAN ANGKLUNG PENTATONIK RAGAM LARAS SEBAGAI INOVASI PERTUNJUKAN MUSIKAL BUDAYA SUNDA DI JAWA BARAT - Irawan dkk., Endah (Paraguna, 2018)
Angklung became part of traditional  music that  develop in the  agrarian  society  in Sundanese culture and Nusantara, Indonesia. This musical instrument is environmentally friendly,  has  a distinctive  sound,  communal, practical,  can be play by  people  at  wide   age   range,   and   very   suitable  for  educational  tools.   The experiment  of  "Ragam  Laras"  Pentatonic  Angklung  is  an   innovation  from  the Sundanese  traditional  angklung.  It  offers  a  new   way   to  grow  and  develop  the creative   industries,   and    at   the   same    time   can   show  the   creativity   on   the development of art education  in Indonesia.  The  initial  idea  began  with  exploring local  potential   to  create   the   image   as   a  creative   industry,   and   looking  for opportunities  to provide  learning  material for the  art  of education-entertainment. The  designed method  starts  from preliminary  research  on  traditional  Sundanese angklung  (in  terms   of organology,  how  to  make   it,   and   musical presentation), design,  making the new  angklung,  and  create new  angklung composition.  In a long term,  the  results   of musical  instruments  and  musical  works   will  spread  to  the public in the educational  sectors  or the tourism industry, through  learning methods, training,  new creation,  workshops, performances,  marketing and  image branding.